2002
DOI: 10.1080/01418610110121076
|View full text |Cite
|
Sign up to set email alerts
|

Icosahedral quasicrystalline and hexagonal approximant phases in the Al-Mn-Be alloy system

Abstract: We report the formation of a primitive icosahedral quasicrystal with increased stability in Al±Mn±Be alloys close to the compound Al 15 Mn 3 Be 2 by melt spinning and injection casting. The crystal structure of this compound was unknown. We show that in as-cast as well as heat treated condition the intermetallic phase H1 has a hexagonal structure with lattice parameters aˆ1:2295 nm and cˆ2:4634 nm. The space group is P6 3 =mmc. In the injection-cast samples, the quasicrystal coexists with another closely relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 5 publications
2
24
0
Order By: Relevance
“…7. The simulated [0 0 1] EDP based on this model agrees with that observed by Kim et al [12]. In this context, it should be mentioned that a chain of four interpenetrated icosahedra occurs also often in orthorhombic approximants of quasicrystals with a lattice parameter of 1.24 nm [31,32].…”
Section: τ-Inflated Phases (P6 3 /Mmc)supporting
confidence: 87%
See 3 more Smart Citations
“…7. The simulated [0 0 1] EDP based on this model agrees with that observed by Kim et al [12]. In this context, it should be mentioned that a chain of four interpenetrated icosahedra occurs also often in orthorhombic approximants of quasicrystals with a lattice parameter of 1.24 nm [31,32].…”
Section: τ-Inflated Phases (P6 3 /Mmc)supporting
confidence: 87%
“…Owing to the large Y atoms, this interpenetrated icosahedral chain is enlarged to a length of 1.4579 nm. Recently, Kim et al [12] reported another hexagonal phase in Al 15 Mn 3 Be 2 with a = 1.2295 nm and they pointed out that this is τ times smaller than that of the -Al 4 Mn. Its structure is possibly related to the four interpenetrated icosahedra part of the 4+2 chain of -Al 4 Mn.…”
Section: τ-Inflated Phases (P6 3 /Mmc)mentioning
confidence: 95%
See 2 more Smart Citations
“…However, it was discovered that beryllium strongly increased the quasicrystalline forming ability in well-known Al-Mn quasicrystalline alloys [9][10][11]. The metastable quasicrystalline phase was present in the microstructure even when conventional casting methods were used; with relatively slow cooling rates in the range of 100 K/s.…”
Section: Introductionmentioning
confidence: 97%